PARTISIPASI MASYARAKAT SEKITAR DANAU BERATAN DALAM KONSERVASI SUMBER DAYA AIR - Rahadiani, A.A. S. Dewi; Sila Dharma, I G.B.; Norken, I N. (JURNAL SPEKTRAN; Vol. 2, No.2, Juli 2014, 2014)
Lakes are one of the surface water resources in Bali Island which supports the socio-economic activities of the community. The growing economic activities either in the tourism or agricultural sector have their effects on the emergence of various problems such as the environmental pollution, shallowness of lakes and erosions. The emergence of various pollutions and the decreased functions of the Lake Beratan is not separable from the intervention of the community living surrounding the lake so that the conservation efforts need the community participation living surrounding the lake. This is based on the idea that the success of the conservation of water resources does not only depend upon the government but the involvement of the community also becomes a key factor. This study aims to identify and analyze the participation of the community living surrounding the Lake Beratan in the conservation of water resources. The number of samples used in this study was 98 respondents gathered by means of purposive sampling in the village of Kembangmerta, the village of Candikuning I and Candikuning II which are located close to the area of Lake Beratan and the majority of the people there use the lake water for daily needs. The community participation is divided into two categories, less participations and good participations, calculated based on Likert scale while the effect of free variables such as age (X 1 ), education (X 2 ), income (X 3 ), length of living (X 4 ), and perception (X 5 ) on bond variables were calculated using discriminating analysis. The result of the study shows that the community participation surrounding Beratan Lake in conserving water resources had been good. The differentiating variables were the age of the respondents and their incomes.
Keywords: community participation, Lake Beratan, conservation, water resources